Preliminary Evaluation of the Acute and Sub-Acute Anti-Inflammatory Activities of Aqueous and Butanol Leaf Fractions of Olax subscorpioidea Oliv. (Olacaceae). - Odoma, Saidi; Umar, Zezi A.; Muhammed, Danjuma N.; Abubakar, Ahmed; Garba, Magaji, M.; Sani, Munir A. (Journal of Phytomedicine and Therapeutics, 2020)
Olax subscorpioidea (Oliv.) leaf is widely used as a traditional remedy for pain, reduction of small tumors, edema, painful swellings, and other inflammatory conditions. Its anti-inflammatory potential in experimental animals has been documented. Furthermore, an anti-inflammatory assay guided fractionation showed that the aqueous and butanol leaf fractions were the most active. This study is aimed at investigating further, the acute and sub-acute anti-inflammatory potentials of the aqueous and butanol leaf fractions in mice and rats. Carrageenan induced paw edema in rats, xylene induced ear edema in mice, and cotton pellet induced granuloma in rats were the models employed for the studies. For each of the methods, four randomly-selected groups of animals (n=5/6) were orally administered with distilled water (1 ml/kg), aqueous or butanol fraction (1,000 mg/kg) and standard drugs (acetylsalicylic acid [ASA] 300 mg/kg or dexamethasone, 1 mg/kg). The aqueous and butanol fractions each showed significant (p < 0.01) inhibition of ear swelling, the fractions also significantly (p < 0.05, p < 0.01) decreased the paw edema, and significantly (p < 0.01) inhibited the granuloma formation. The result of the study suggests that aqueous and butanol leaf fractions of Olax subscorpioidea are effective against acute and sub-acute inflammation.
Keywords: Carrageenan; Cotton-pellet granuloma; Inflammation; Olax subscorpioidea; Xylene